2016
DOI: 10.18632/oncotarget.13747
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-497 inhibits thyroid cancer tumor growth and invasion by suppressing BDNF

Abstract: miR-497 reportedly plays critical roles in tumor development and progression in many types of cancers. We therefore investigated the function and underlying mechanism of miR-497 in thyroid cancer. We found that miR-497 is downregulated in thyroid cancer tissues, and that miR-497 levels are negatively correlated with advanced clinical stage and lymph node metastasis. Overexpressed miR-497 suppressed thyroid cancer cell proliferation, colony formation, migration, and invasion in vitro, and inhibited tumorigenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 35 publications
3
43
0
Order By: Relevance
“…In the context of PTC, accumulating evidence suggested that the abnormal expression of miRNAs play a pivotal role in the development and progression of PTC (Leonardi et al, ; Aragon Han et al, ). For instance, a previous study found that miR‐497 exhibits its anti‐proliferative and anti‐metastatic effects on thyroid cancer by repressing BDNF and its downstream signaling pathways (PI3K/AKT) (Wang et al, ). Wen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of PTC, accumulating evidence suggested that the abnormal expression of miRNAs play a pivotal role in the development and progression of PTC (Leonardi et al, ; Aragon Han et al, ). For instance, a previous study found that miR‐497 exhibits its anti‐proliferative and anti‐metastatic effects on thyroid cancer by repressing BDNF and its downstream signaling pathways (PI3K/AKT) (Wang et al, ). Wen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Study of osteosarcoma cells revealed that the inhibitory impact of miR‐497‐5p on proliferation and invasion of human MG‐63 osteosarcoma cells could be mediated by downregulation of angiomotin (Ruan, Wang, Feng, Xue, & Zhang, 2016). Overexpression of miR‐497‐5p in human thyroid cell line TPC‐1 suppressed a brain‐derived neurotrophic factor expression following inhibition of tumor growth and invasion (Wang et al, 2017). Analysis of miR‐497‐5p in colorectal cancer patients indicated a significant downregulation of miR‐497‐5p in CRC tumors (Guo et al, 2013; Qiu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-497-5p in human thyroid cell line TPC-1 suppressed a brain-derived neurotrophic factor expression following inhibition of tumor growth and invasion (Wang et al, 2017). Analysis of miR-497-5p in colorectal cancer patients indicated a significant downregulation of miR-497-5p in CRC tumors (Guo et al, 2013;Qiu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that miR-141 suppressed TC cell growth and metastasis by suppressing insulin receptor substrate 2, indicating that miR-141 may serve as a potential therapeutic target for the treatment of patients with TC (31). Furthermore, miR-497 is also considered to be a TC tumor suppressor that acts by repressing brain derived neurotrophic factor (32). A previous study also indicated that miR-7 may function as a tumor suppressor by directly targeting serine/threonine protein kinase 1, potentially serving as a novel therapeutic target for TC (30).…”
Section: Discussionmentioning
confidence: 99%